Technical and Operational Feasibility, for the business analysis, of running an Autopista Ferroviaria with Iberian track gauge between Port of Algeciras and Zaragoza-Plaza - Escobar de la Iglesia, Jaime; Larrodé, Emilio (Jornada de Jóvenes Investigadores del I3A, 2020)
The aim of this study is to evaluate the feasibility to run an Autopista Ferroviaria (AF) with Iberian track gauge from a technical and operational point of view in order to analyse the business model in the short term